Mermaid baby or sirenomelia: a lethal congenital anomaly - Ram Jeewan Singh; Bijay Kumar Suman; Keerthana Bachala; Amit Kumar; Rashi Rashi; Amit Kumar Sinha (International Journal of Contemporary Pediatrics, 2023)
Mermaid syndrome is a very rare, lethal congenital anomaly. It is associated with other congenital anomalies and is incompatible with life. Typical clinical features are fused lower limb from perineum to ankle and single umbilical artery. Etiology is multifactorial and is extreme form of caudal regression syndrome. When diagnosed in early gestation, termination of pregnancy may be considered.